Impact of headache on sickness absence and utilisation of medical services: a Danish population study. Issue 4 (August 1992) - Rasmussen, B K; Jensen, R; Olesen, J
Abstract : STUDY OBJECTIVE–The aim was to study the extent and type of health service utilisation, medication habits, and sickness absence due to the primary headaches. DESIGN–This was a cross sectional epidemiological survey of headache disorders in a general population. Headache was diagnosed according to a structured interview and a neurological examination using the criteria of the International Headache Society. SETTING–A random sample of 25-64 year-old individuals was drawn from the Danish National Central Person Registry. All subjects were living in the Copenhagen County. PARTICIPANTS–740 subjects participated (76% of the sample); 119 had migraine and 578 had tension type headache. MAIN RESULTS–Among subjects with migraine 56% had, at some time, consulted their general practitioner because of the migraine. The corresponding percentage among subjects with tension type headache was 16. One or more specialists had been consulted by 16% of migraine sufferers and by 4% of subjects with tension type headache. The consultation rates of chiropractors and physiotherapists were 5-8%. Hospital admissions and supplementary laboratory investigations due to headache were rare (< 3%). Half of the migraine sufferers and 83% of subjects with tension type headache in the previous year had managed with at least one type of drug in the current year. Acetylsalicylic acid preparations and paracetamol were the most commonly used analgesics. Prophylaxis of migraine was used by 7%. In the preceding year 43% of employed migraine sufferers and 12% of employed subjects with tension type headache had missed one or more days of work because of headache. Most common was 1-7 days off work. The total loss of workdays per year due to migraine in the general population was estimated at 270 days per 1000 persons. For tension type headache the corresponding figure was 820. Women were more likely to consult a practitioner than men, whereas no significant sex difference emerged as regards absenteeism from work. CONCLUSIONS–The impact of the headache disorders on work performance in the general population is substantial, and the disorders merit increased attention.